EXPERIENCE IN THE USE OF BISOPROLOL IN THE TREATMENT OF OUTPATIENT HYPERTENSIVE PATIENTS AFTER STROKE - I. I. Esenova; L. N. Lisenker (Столичная издательская компания, 2015)
Aim. To study the dynamics of blood pressure (BP), heart rate (HR), the sympathetic-vagal balance in patients with arterial hypertension (HT) III stage after stroke during therapy based on bisoprolol 5-10 mg/day. Material and methods. Patients (n=12) with HT stage III with stroke history were examined. Age of the patients was 62±7.4 years old. Laboratory tests, BP monitoring, evaluation of the ratio of low frequency (LF) and high frequency (HF) components of HR variability and average daily HR determination were performed in all patients at baseline, after 14 and 34 days after therapy initiation. Bisoprolol was administered at dose of 5-10 mg/day. Results. BP decreased to the target level in all patients after 14 days of treatment and persisted through 34 days. Average daily HR and LF/HF ratio decreased, reaching the optimal values after 34 days. Significant dynamics in metabolic parameters and side effects were not found. Conclusion. Target BP levels, a significant decrease in HR and sympathetic activity, increase in parasympathetic activity of the autonomic regulation occurred since 14-th day of therapy based on bisoprolol (5-10 mg/day). The received effects allowed patients to continue rehabilitation therapy, accompanied with physical exertion.